answersLogoWhite

0

f(x) = x/2

Then the differential is lim h->0 [f(x+h) - f(x)]/h

= lim h->0 [(x+h)/2 - x/2]/h

= lim h->0 [h/2]/h

= lim h->0 [1/2] = 1/2

f(x) = x/2

Then the differential is lim h->0 [f(x+h) - f(x)]/h

= lim h->0 [(x+h)/2 - x/2]/h

= lim h->0 [h/2]/h

= lim h->0 [1/2] = 1/2

f(x) = x/2

Then the differential is lim h->0 [f(x+h) - f(x)]/h

= lim h->0 [(x+h)/2 - x/2]/h

= lim h->0 [h/2]/h

= lim h->0 [1/2] = 1/2

f(x) = x/2

Then the differential is lim h->0 [f(x+h) - f(x)]/h

= lim h->0 [(x+h)/2 - x/2]/h

= lim h->0 [h/2]/h

= lim h->0 [1/2] = 1/2

User Avatar

Wiki User

11y ago

Still curious? Ask our experts.

Chat with our AI personalities

RossRoss
Every question is just a happy little opportunity.
Chat with Ross
DevinDevin
I've poured enough drinks to know that people don't always want advice—they just want to talk.
Chat with Devin
JordanJordan
Looking for a career mentor? I've seen my fair share of shake-ups.
Chat with Jordan
More answers

f(x) = x/2

Then the differential is lim h->0 [f(x+h) - f(x)]/h

= lim h->0 [(x+h)/2 - x/2]/h

= lim h->0 [h/2]/h

= lim h->0 [1/2] = 1/2

User Avatar

Wiki User

11y ago
User Avatar

Add your answer:

Earn +20 pts
Q: How do you differentiate x over 2?
Write your answer...
Submit
Still have questions?
magnify glass
imp